Hepatic and biochemical repercussions of a polyunsaturated fat-rich hypercaloric and hyperlipidic diet in Wistar rats - Burlamaqui,Idália M. B. (2011)
CONTEXT: Non-alcoholic fatty liver disease is characterized by lipid deposits in the hepatocytes and has been associated with obesity, dyslipidemia and type-2 diabetes. It is considered a hepatic manifestation of the metabolic syndrome, of which the main component is insulin resistance leading to hyperinsulinemia and increased production of inflammatory cytokines. Saturated fat promotes hypertriglyceridemia and hyperinsulinemia, reduces levels of high-density cholesterol and increases levels of low-density cholesterol, while polyunsaturated fat is associated with hypolipidemic, antiinflammatory and imunoregulating action. OBJECTIVE: To evaluate the hepatic and biochemical repercussions of a polyunsaturated fat-rich diet in Wistar rats. METHODS: Twenty-two rats were distributed equally in two groups: GI - standard diet (Biobase Bio-tec Ratos e Camundongos®) providing 3.000 kcal/kg and GII - hypercaloric and hyperlipidic diet providing 4.250 kcal/kg (ω-6:ω-3 = 3:1). The animals were euthanized after 23 weeks of experiment. The weight, biochemical parameters and hepatohistological changes were registered. RESULTS: Findings were submitted to variance analysis with the level of statistical significance at 5%. The average weight did not differ significantly between the groups at baseline (P = 0.711), but was greater in Group II by the end of the experiment (P = 0.000). The levels of triglycerides (P = 0.039), total cholesterol (P = 0.015) and HDL (P = 0.005) were higher in Group I than in Group II. Macrovesicular steatosis was significantly more common in Group II than in Group I (P = 0.03). CONCLUSION: Hypercaloric and hyperlipidic diet rich in polyunsaturated fat promotes weight gain and favors the development of hepatic steatosis while reducing serum levels of triglycerides, total cholesterol and HDL.